Keamanan Komunitas dan Tata Kelola Perbatasan: Studi Kasus Wilayah Baarle-Nassau dan Baarle-Hertog - Perbawani, Firsty Chintya Laksmi (Global and Policy Journal of International Relations, 2025)
This article examines community security and border governance through a case study of Baarle-Nassau (Netherlands) and Baarle-Hertog (Belgium), an enclave-exclave region marked by extreme spatial and administrative fragmentation, comprising 30 enclaves in total; 22 Belgian enclaves within the Netherlands and 8 Dutch counter-enclaves within Belgian territory. Using a qualitative-descriptive method and the UNDP’s (2012) framework of community security, this article explores seven key dimensions: (1) historical-rooted spatial fragmentation reflects unresolved conflict legacies; (2) civic participation is institutionalized through joint bodies like Gemeenschappelijke Orgaan Baarle (GOB) and Benelux Grouping for Territorial Cooperation (BGTC); (3) multi-sectoral collaboration enables dual delivery of services such as education and emergency response; (4) strong social cohesion is fostered through inclusive events and symbolic integration; (5) access to reliable public services is ensured via shared schools and infrastructure; (6) the absence of intercommunal violence demonstrates effective boundary normalization; and (7) local institutions exhibit strong capacity for cross-border coordination. These findings are situated within the broader framework of border governance, showing how overlapping jurisdictions and divided territories give rise to mosaic sovereignty, where functional cooperation overrides territorial rigidity, and everyday bordering, where symbolic negotiation and civic routines normalize fragmentation. The Baarle case thus illustrates how human security and border governance can coexist through flexible, inclusive, and community-centered practices.